Information asymmetry and the dismissal of newly appointed CEOs: an empirical investigation - Zhang, Yan (Strategic Management Journal, 2008)
Abstract Why are some newly appointed CEOs (i.e., those with tenure of three years or less) dismissed while others are not? Drawing upon previous reseach on information asymmetry and adverse selection in CEO selection, I argue that the board of directors may make a poor selection at the time of CEO succession, and as a result, must dismiss the appointee after succession when better information about him/her is obtained. Therefore, the level of information asymmetry at the time of succession increases the likelihood of dismissal. With data on 204 newly appointed CEOs, the results of this study support this argument. After controlling for alternative explanations of CEO dismissal (e.g., firm performance and political factors), the results show that the likelihood of dismissal of newly appointed CEOs is higher in outside successions and/or if the succession follows the dismissal of the preceding CEO. Further, if at the time of succession, the firm's board has a nominating committee that is independent and/or on which outside directors have few external directorships, the likelihood of dismissal is lower. Contributions to the CEO dismissal/succession literature are discussed. Copyright © 2008 John Wiley & Sons, Ltd.